MENCEGAH BRAIN ROT: PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA VIDEO YOUTUBE DALAM MENGUJI KEMAMPUAN ANALISIS PESERTA DIDIK - Deni Nasir Ahmad; Giry Marhento; Zakiah Fithah A’ini; Aulia Masruroh; Nurma Tambunan; Luluk Setyowati; Arum Sanjayanti (Jurnal Penelitian Pendidikan IPA, 2026)
The phenomenon of brain rot, or the decline in analytical thinking skills due to passive consumption of digital content, is a new challenge in modern education. This study aims to test whether YouTube video-based learning improves students' analytical skills compared to conventional learning. The term "brain rot" has garnered widespread attention and has been discussed in both popular and academic literature recently; several articles and reviews have suggested a link between consuming short/shallow content and decreased concentration, cognitive overload, or reduced deep thinking. social media has positive impacts, such as a means for socializing, self-expression, seeking entertainment, obtaining information, building networks, and supporting the educational process, its negative side is also real. The research method used a quantitative approach with a quasi-experimental design. The study, conducted before and after the use of image learning media, significantly improved students' analytical skills. The results of the analysis of the analytical thinking skills test revealed changes in learning, indicating an increase. This means that the average sample remained in a normal brain state and did not experience a decline or brain decay in their analytical skills. The conclusion of this study is that targeted learning using YouTube videos can prevent brain rot by improving students' analytical skills.